Reconsidering the unemployment and crime relationship: Variation by age group and historical period - Britt, Chester L. - (Journal of quantitative criminology, 1997)
Although considerable research has examined the direct effects of age and economic conditions on crime, relatively little work has investigated the joint influence that age and unemployment may have on rates of criminal behavior. This study extends prior research on the unemployment-crime relationship by testing simultaneously for (1) variation in the unemployment-crime relationship by age group and (2) variation in the unemployment-crime relationship over time. Age-specific arrest and unemployment time-series data for the United States from 1958 to 1995 are used to test these hypotheses. The two main findings indicate that (1) unemployment has a greater motivational effect on property crime among youth and young adults and (2) the unemployment-crime relationship varies over time, but in a way that appears to be more random than systematic. The implications for future research are discussed.